Электрооборудование автомобилей ВАЗ - Литвиненко Владимир Васильевич (Патриот, 1990)
Экземпляры: ф.3 (1991) / Инвентарный номер: 32954 / Цена: / Сис.шифр: 39.33 / Авт.знак: Л 64 / ГРНТИ: 73.31.41 / ББК: 39.335